CLASSICAL EXPERIMENTS IN CINE MUSIC: IN THE CONTEXT OF ASAVARI THAT: सिने संगीत में शास्त्रीय प्रयोग: आसावरी थाट के संदर्भ में - Jain, Rupali (International Journal of Research -GRANTHAALAYAH, 2015)
We should consider the beginning of film music with the advent of speaking films. In the era of silent films, there used to be an orchestra near the screen in big cities, playing music suited to the changing emotions of the on-screen story, but the lyrics also came as an integral part of the film along with the speaking films and musicians Also has a separate identity. So the first cine music and its composer, we will consider Feroz Shah Mistry, the composer of the first speaking film "Alamara", released on 14 March 1931 at the Majestic Cinema in Mumbai and the first cine song "De De Khuda Ke Naam Pe Pyare". , There is strength to give away, if you want something, if you ask me, you will have the courage to accept it. The singer of this song, the actor of the same film, WM. It was Khan, who sang it in the character of Fakir. The song was composed with a tabla and a harmonium, but unfortunately it could not be recorded, the songs of the ragas in the film also came from the same film, which was sung by Munni Bai, "Apne Maula Ki Main Jogan" Banungi ", the song was based on the raga" Bhairavi ". फिल्म संगीत का आरंभ हमें बोलती फिल्मों के आगमन से ही मानना चाहिए। मूक फिल्मों के दौर में बड़े शहरों में स्क्रीन के पास एक आॅरकेस्ट्रा रहा करता था, जो परदे पर चल रही कहानी के बदलते भावों के अनुकूल संगीत बजाया करता था, पर बोलती फ़िल्मों के साथ गीत-संगीत भी फ़िल्म का अंतरंग हिस्सा बनकर आए और संगीतकार की भी एक अलग पहचान बनी। अतः प्रथम सिने संगीत और उसका संगीतकार हम 14 मार्च, 1931 को मुंबई के मैजेस्टिक सिनेमा में रिलीज प्रथम बोलती फिल्म ’’आलमआरा’’ के संगीतकार फिरोज शाह मिस्त्री को ही मानेंगे तथा पहला सिने गीत ’’दे दे खुदा के नाम पे प्यारे’’, ताकत है गर देने की, कुछ चाहे तो अगर माँग ले मुझसे, हिम्मत हो गर लेने की ’’ को मानेंगे। इस गीत के गायक इसी फिल्म के अभिनेता डब्ल्यू.एम. खान थे, जिन्होंने इसे फ़कीर के किरदार मंे गाया था। इस गीत को मात्र तबले और एक हारमोनियम के साथ सृजित किया गया था, किंतु दुर्भाग्यवश इसका रिकार्ड नहीं बन सका, फिल्म में रागों पर आधारित गीतों का चलन भी इसी फिल्म से आया, जिसमें मुन्नी बाई का गाया, ’’अपने मौला की मैं जोगन बनूँगी ’’, यह गीत राग ’’भैरवी’’ पर आधारित था।